Seismic Fragility Analysis of Buildings Based on Double-Parameter Damage Models considering Soil-Structure Interaction - Panpan Zhai; Peng Zhao; Yang Lu; Chenying Ye; Feng Xiong (Advances in Materials Science and Engineering)
Most conventional seismic fragility analyses of RC buildings usually ignore or greatly simplify the soil-structure interaction (SSI), and the maximum interstory drift ratio (MIDR) is often adopted to establish seismic fragility curves. In this work, an eight-story RC building was designed to study the influence of the SSI on the seismic fragility of RC buildings. Three double-parameter damage models (DPDMs) were considered for the fragility assessment: the Park–Ang model, the Niu model, and the Lu–Wang model. Results show that considering SSI induces a higher fragility than that of the fixed model and that employing the DPDMs for the fragility analysis provides more reasonable results than those evaluated using the MIDR damage index.